Research on several key technologies of satellite Internet - Gengxin ZHANG; Yunfeng WANG; Xiaojin DIGN; Tao HONG; Ziwei LIU; Chen ZHANG (Tongxin xuebao)
Satellite Internet has the ability of global seamless coverage, which will be an important part of the future land-sea-air-space integrated network.Firstly, the architecture of satellite Internet was discussed, which included the general composition of the system, networking mode, working process, etc.Secondly, the methods of modeling broadband and narrowband traffic were proposed to extract the uneven space-time distribution characteristics of traffic for satellite Internet.Then, the co-frequency interference of spectrum-sharing was analyzed, showing that there would be more serious co-frequency interference among different non-geostationary satellite orbit (NGSO) constellations in the future.Next, the schemes of both beamforming design for low earth orbit satellite and beam-hopping design for high orbit satellite were explored, which could significantly improve the system capacity through efficient mining of space-domain resources.Finally, the development prospect of several technologies of satellite Internet were given.